Design of an efficient Weighted Trust Evaluation System for Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2014)
Conventional trust management techniques developed for wired and wireless sensor networks are not well suited for applications due to their higher memory and power consumption. To overcome this an efficient  Weighted Trust Evaluation System for Wireless Sensor Networks (WTES-WSN), is proposed in this paper. A trust detection system is proposed based on node identities and an enhanced trust evaluating approach is defined in cooperation between cluster heads.  This approach significantly increases the system efficiency and reduces the cost of trust evaluation. Moreover a novel scheme based on weighted-trust evaluation to detect malicious nodes is proposed in this paper. Also, theoretical and simulation results show that this scheme provides less memory, energy, and communication overheads as compared to the current trust management schemes. Furthermore, this approach  enables us to detect and prevent malicious, selfish, and faulty nodes.